The Configurational Perspective A View of Educational Knowledge Production and Utilization - Guba, Egon G.; Clark, David L.; Council for Educational Development and Research, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
The method by which the systems view of educational knowledge production and utilization (KPU) has emerged from the federal experience of the last twenty years (1954-1974) is discussed. The impact of this approach on more recent federal KPU programs is considered, and the suitability of such an approach with regard to meeting the proposed criteria of "completeness, balance, and realism" in the educational milieu is debated. An alternative approach, the configurational view, is contrasted with the systems approach, and the suggestion is made that use of the configurational model to generate federal policies for educational KPU would result in more productive relationships between both federal funding agencies and KPU units in the field, as well as between KPU units themselves. (LH)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Development; Educational Policy; Educational Research; Federal Government; Government Role; Productivity; Relationship; Research Utilization; Systems Approach; Historical Materials; Information Analyses; Reports, Evaluative